Administration of productive organizations from sociology - Ariosto Carita Choquecahua; Segundo Ortiz-Cansaya; Anibal Javier Cutipa-Laqui; Ana Cecilia De Paz Lazaro; Yorrlanka Evelin Damian Espinoza (Universidad Ciencia y Tecnología, 2022)
A bibliographical study on the administration of productive organizations is presented, considering a social perspective. Making diagnostic evaluations in labor organizations is of great social interest to intervene professionally in the generation of strategies for production, economic and social development, and theirmonitoring and control. In Latin America, there is a diversity of social situations, in each of the productive sectors, and they are also affected by the external economy, due to their dependence on the large industrial countries. Different academic and scientific elements that show the social scenarios in the productive sectors are evaluated, considering the cultural differences of Latin America, and their individual concerns, which commit them to integrated local development. The main results of this analysis show that the Latin American productive sectors must focus their attention on integration, despite social distinctions, to promote a solid and productive block on the continent.